Cardiovascular Risks and Risk Stratification in Inflammatory Joint Diseases: A Cross-Sectional Study - Yagensky, Vasyl; Schirmer, Michael (Frontiers in Medicine, 2022)
BACKGROUND: It is well established that patients with inflammatory joint diseases (IJD) have an increased cardiovascular (CV) mortality and morbidity. According to the 2016 EULAR recommendations on CV risk management, rheumatologists should ensure appropriate management of CV risk in rheumatoid arthritis (RA) and other IJDs. The aim was to assess the CV risk and CV disease in Middle-European patients with IJD. METHODS: A retrospective chart review was performed for CV risk factors and CV disease in out-patients of a rheumatology outpatient clinic. CV risk was assessed according to the 2016 European Guidelines on CV disease prevention, and also using 2 other approaches to compare the results with data from a Norwegian and a Spanish cohort. RESULTS: Out of 432 patients, prevalence of CV disease reached from 8.7% in spondyloarthritis (SpA) and 12.8% in psoriatic arthritis (PsA) to 18.7% in RA patients. The number of CV risk factors did not differ between RA, SpA, PsA and non-inflammatory rheumatic disease (NIRD) patients (with 1.68+/-0.13, 1.70+/-0.13, 2.04+/-0.16 and 1.78+/-0.34, respectively). CV risk assessment could be performed in 82 patients after exclusion because of missing data and age. Stratification according to ESC guidelines showed low in 50.0%, moderate in 12.2%, high in 20.7% and very high CV risk in 17.1% of patients aged between 40 to 65 years. CV risk in the Middle-European IJD patients was higher than in the German general population (p=0.004), and similar to the Norwegian IJD patients, although Middle-European PsA patients were at higher risk than the Norwegian patients (p = 0.045). Compared to the Spanish patients, Middle-European IJD patients were more likely assigned to the high- to very high-risk group (34.2% vs. 16.2%, p<0.001), especially in RA disease (49.1% vs. 21.0%, respectively, p<0.001). DISCUSSION: High prevalence of established CV disease together with high CV risk in IJD patients urge for increased vigilance for CV risk factors followed by appropriate interaction by the treating physicians. The prospective use of an international CV risk assessment tool will allow not only estimation of the individual CV risk but also provide data for direct comparisons with the general population and other international cohorts.